Synergetic grain refinement and ZrB2 hardening in in-situ ZrB2/AA4032-type composites by ultrasonic assisted melt treatment - S. Chankitmunkong; D.G. Eskin; C. Limmaneevichitr; P. Pandee (My University, 2023)
In this work, the effects of ultrasonic treatment on in-situ ZrB2 particle-reinforced AA4032-based composites were studied. The composites were synthesized from Al–K2ZrF6–KBF4 system via an in-situ melt reaction. The phase composition, macrostructure characteristics, hardness and tensile properties of the composites were investigated. The results showed that the addition of in-situ submicron ZrB2 particles into the composites resulted in grain refinement, and the increased hardness and tensile properties. The ultrasonic treatment effectively enhanced the uniformity of in-situ ZrB2 distribution, which further enhanced the structure and mechanical properties of the composites. The mechanisms of the ultrasonic treatment in the improvement of in-situ particle distribution and mechanical properties of the composites were discussed.
Keywords: Hardening (computing); Work hardening; Aluminum Alloys Composites Properties